2007
DOI: 10.1073/pnas.0609498104
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus X protein enhances androgen receptor-responsive gene expression depending on androgen level

Abstract: Persistent hepatitis B virus (HBV) infection is a major risk of hepatocellular carcinoma (HCC). One intriguing feature of HBVrelated HCC is the male predominance, with a male to female ratio of 5-7:1. This dominance has been attributed to the elevated androgen level and the enhanced androgen receptor (AR)-mediated activity in the host. How HBV infection and AR signaling modulate HCC is unknown. We investigated whether the HBV nonstructural protein, X protein (HBx) could cooperate with the AR signaling pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
122
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 132 publications
(129 citation statements)
references
References 56 publications
7
122
0
Order By: Relevance
“…These results are in agreement with the finding that AR and miR-216a were concordantly overexpressed in clinical specimens, while an inverse correlation between TSLC1 and miR-216a was also identified in these liver tissues (25). The presence of the hepatitis B virus (HBV) X protein (HBx) can further augment the effect of AR-mediated miR-216a transcription, due to its known ability to enhance AR activity (38,39). Notably, recent studies have indicated that miRNAs, including miR-224, miR-221, miR-122a and miR-223, demonstrate deregulated expression patterns in male HCC patients (25).…”
Section: Ar Promotes Hepatocarcinogenesissupporting
confidence: 80%
“…These results are in agreement with the finding that AR and miR-216a were concordantly overexpressed in clinical specimens, while an inverse correlation between TSLC1 and miR-216a was also identified in these liver tissues (25). The presence of the hepatitis B virus (HBV) X protein (HBx) can further augment the effect of AR-mediated miR-216a transcription, due to its known ability to enhance AR activity (38,39). Notably, recent studies have indicated that miRNAs, including miR-224, miR-221, miR-122a and miR-223, demonstrate deregulated expression patterns in male HCC patients (25).…”
Section: Ar Promotes Hepatocarcinogenesissupporting
confidence: 80%
“…7 Our previous study showed that HBx could enhance the transcriptional activity of AR, which leads to an increased risk of HCC. 8 The current study further disclosed a new role of AR in liver carcinogenesis, namely the activation of HBV transcription and replication. A positive regulatory loop might exist between the increase in AR transcription activities by HBx, and the increase in HBV (HBx) gene expressions through the ligand-stimulated AR pathway (summarized in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, we recently showed that HBV X protein (HBx) can enhance the transcriptional activity of AR in a ligand concentration-dependent manner, which may explain the male predominance of HBV-related HCC. 8 Because of the …”
mentioning
confidence: 99%
“…HBx, which has a size of ~17 kDa, can physically bind to AR [49]. HBx-mediated enhancement of AR activity is androgen-dependent and could be mediated through indirect mechanism involving calcium and c-Src signaling pathways [50]. HBx enhances the AR transcriptional activity through two kinases: c-Src and glycogen synthase kinase-3beta kinase [51].…”
Section: Androgen Receptor-mediating Signaling In Hbvrelated Hepatocamentioning
confidence: 99%